2015
DOI: 10.1002/2015jg002923
|View full text |Cite
|
Sign up to set email alerts
|

Effects of episodic flooding on the net ecosystem CO2 exchange of a supratidal wetland in the Yellow River Delta

Abstract: Episodic flooding due to intense rainfall events is characteristic in many wetlands, which may modify wetland-atmosphere exchange of CO 2 . However, the degree to which episodic flooding affects net ecosystem CO 2 exchange (NEE) is poorly documented in supratidal wetlands of coastal zone, where rainfall-driven episodic flooding often occurs. To address this issue, the ecosystem CO 2 fluxes were continuously measured using the eddy covariance technique for 4 years (2010-2013) in a supratidal wetland in the Yell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
80
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 66 publications
4
80
0
Order By: Relevance
“…Furthermore, the model results indicated that WTD had a larger influence than temperature on respiration (Figure ). Our finding of lower respiration rates during inundation is consistent with observations from other coastal wetland sites (Barr et al, , ; Forbrich & Giblin, ; Han et al, ; Heinsch et al, ; Li et al, ; Xie et al, ). In addition, Xie et al () also observed a periodic fluctuation of R eco in summer driven predominantly by water levels rather than temperature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the model results indicated that WTD had a larger influence than temperature on respiration (Figure ). Our finding of lower respiration rates during inundation is consistent with observations from other coastal wetland sites (Barr et al, , ; Forbrich & Giblin, ; Han et al, ; Heinsch et al, ; Li et al, ; Xie et al, ). In addition, Xie et al () also observed a periodic fluctuation of R eco in summer driven predominantly by water levels rather than temperature.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of water levels on R eco is likely explained by the suppression of CO 2 efflux from the soil as water creates a barrier against gas diffusion (Guo et al, ; Han et al, ; Heinsch et al, ), which is supported by the instantaneous drop in nighttime respiration with flooding of the marsh, despite incoming warmer waters causing an increase in T soil (Figure ), and the near‐synchronous relationship between NEE and WTD at the multiday scale (Figure ). As such, standing water and water in pores restricted gas exchange between the marsh surface and the atmosphere such that R eco increased as water levels decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of microbial respiration in soil depends primarily on the availability of O 2 and C in the soil, and on soil temperature and soil moisture, although respiration may also be inhibited when soil water content is either too high or too low (Linn & Doran, 1984). When organic-rich salt marsh sediments are drained, O 2 diffuses deeper into the sediment column, stimulating oxic respiration and enhancing decomposition rates and CO 2 flux out of the soil (Chivers, Turetsky, Waddington, Harden, & McGuire, 2009;Han et al, 2015;Jimenez et al, 2012). Multiple studies have demonstrated that a drop in the water table could accelerate the CO 2 efflux as much as 50 times faster, possibly due to a combination of increased aerobic oxidation and relief from the ionic stress caused by saltwater inundation (Chambers et al, 2013;Krauss, Whitbeck, & Howard, 2012;Moore & Knowles, 1989;Strakova, Penttila, Laine, & Laiho, 2012;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in YRD have reported the soil organic carbon (SOC) budget13, the distribution characteristics of SOC and nutrients stoichiometry in new-born coastal wetlands1819, the nutrients exchange between land and atmosphere202122. However, whole ecosystem scale nutrients information regarding the biogeochemical processes of C, N and P responsible for regulating the spatial distribution related land use and salinity studies in the YRD coastal systems is still lacking.…”
mentioning
confidence: 99%